Freeze tolerance of the yeast Torulaspora delbrueckii: cellular and biochemical basis - Araújo, Cecília Alves (2004)
The freeze-stress responses to prolonged storage at - 20 °C in Torulaspora delbrueckii PYCC5323 were investigated. In this yeast no loss of cell viability was observed for at least 120 days during freezing at - 20ºC, whereas a loss of 80% was observed in a commercial baker's yeast after 15 days. In the former strain, freeze resistance was dependent on an adaptation process. The primary cell target of freeze stress was the plasma membrane, preservation of it’s integrity being related with a lower increase of lipid peroxidation and with higher resistance to H2O2, but not with intracellular trehalose concentration.